Sex addiction : it is a silent problem - Negrete, Yadith Seleme; Negrete Ruiz, Indira; Celedón Rivero, José (Pensando Psicología, 2010)
Sex addiction is an uncontrollable sex hypersexuality everything from sex with other people until consumption of pornography or masturbation. Hypersexuality is one of the least known and visible units, as people who have it tend to keep it hidden, and conceal, especially with people I know. Addictions in general, once they become embedded as such, act as a repetitive cycle, following steps usually more or less similar. Culture plays an important role and invisible the problem of sexual addiction because in one way or another becomes a reinforcer of behavior.
Keywords: sex addiction; problem quiet; gender and culture